PERAN VITAL RELAWAN PAJAK DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Lioe, Nathaniel Edbert; Wijaya, Purnamawati Helen (Jurnal Serina Abdimas, 2024)
The tax volunteer activity, which took place between January until March 2023, was primarily aimed at providing support to individual taxpayers in filing their annual tax returns. This activity is carried out offline at Kantor Pelayanan Pajak during March 2023. In addition to assisting in the filing process, tax volunteers also play a role in raising public awareness of tax obligations. The benefits of this activity are diverse, including improved communication skills and a deeper understanding of taxation. Tax volunteers act as facilitators who provide technical guidance to taxpayers, helping them understand the filing process, as well as understanding the potential tax breaks available. Through direct interaction with the public, tax volunteers also develop communication skills, understand the complexity of tax regulations, and enhance their understanding of tax practices. Thus, these tax volunteer activities not only fill an important gap in tax education and support, but also develop valuable skills in addressing tax issues, which become valuable assets for the development of the community and the country.